(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Objective: The aim of the study was to investigate the impact of smoking on thyroid gland volume, echotexture, nodularity, and function. Method: This prospective observational study was conducted in the department of ultrasonography at the Institute of Nuclear Medicine & Allied Sciences, Mitford, from October 2023 to December 2023. A total of 54 subjects of both sexes were randomly selected who had no known thyroid disorders. Among them, 24 were smokers and 30 were nonsmokers. The Esaote My Lab Ultrasound Machine was used to perform a sonographic examination of the thyroid gland, and the hormonal assay was performed using the RIA method. Result: We found a moderately positive correlation between smoking habit and thyroid gland volume (rs = 0.494, p< 0.01) and smoking duration and thyroid gland volume (rs = 0.478, p< 0.01). No significant correlation was found between smoking habits and thyroid echotexture, nodularity, and function. Conclusion: Smoking presents a statistically significant goitrogenic effect on thyroid gland volume but has no impact on echotexture, nodularity, or function. Bangladesh J. Nuclear Med. 26(2): 124-128, 2023